Respuesta :
f(x) = 4 - x^2
g(x) = 6x
(g - f)(x) = g(x) - f(x) = 6x - (4 - x^2) = 6x - 4 + x^2
(g - f)(3) = 6(3) - 4 + 3^2
g(x) = 6x
(g - f)(x) = g(x) - f(x) = 6x - (4 - x^2) = 6x - 4 + x^2
(g - f)(3) = 6(3) - 4 + 3^2
Answer:
Option (c) is correct.
[tex](g-f)(3)=6(3)-4+(3)^2[/tex]
Step-by-step explanation:
Given : [tex]f(x)=4-x^2\\\\ g(x)=6x[/tex]
We have to find the expression is equivalent to (g –f)(3)
That is g(3) - f(3)
First find g(x) - f(x)
We have,
[tex]g(x)-f(x)=6x-(4-x^2)\\\\ g(x)-f(x)=6x-4+x^2[/tex]
Now, put x = 3
We have,
[tex]g(3)-f(3)=6(3)-4+(3)^2[/tex]
Thus, [tex](g-f)(3)=6(3)-4+(3)^2[/tex]